The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0104-66322009000200014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of AlMCM-41 synthesized with rice husk silica and utilization as supports for platinumiron catalysts

Abstract: -RH-MCM-41 was synthesized by using silica from rice husk and further modified to increase acidity by adding Al with grafting method with Si/Al ratio of 75 and 25. The resulting materials were referred to as RH-AlMCM-41(75) and RH-AlMCM-41(25). The XRD spectra of all RH-AlMCM-41 confirmed a mesoporous structure of MCM-41. Surface areas of all RH-AlMCM-41 were in the range of 700-800 m 2 /g, lower than that of the parent RH-MCM-41, which was 1230 m 2 /g. After Al addition the Si/Al ratios of RHAlMCM-41(75) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Several technological alternatives have been associated in the literature with the use of RH and RHA: production of silica and silicon carbide, using the ashes like filler in polymers, in concrete, production of silicates, zeolite synthesis (Chumee et al, 2009) and use as an adsorbent of heavy metals in synthetic wastewater (Srivastava et al, 2006;Naiya et al, 2009;Krishnani et al, 2008;Ye et al, 2010;Bhatnagar and Sillanpaa, 2010;Ahmaruzzaman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several technological alternatives have been associated in the literature with the use of RH and RHA: production of silica and silicon carbide, using the ashes like filler in polymers, in concrete, production of silicates, zeolite synthesis (Chumee et al, 2009) and use as an adsorbent of heavy metals in synthetic wastewater (Srivastava et al, 2006;Naiya et al, 2009;Krishnani et al, 2008;Ye et al, 2010;Bhatnagar and Sillanpaa, 2010;Ahmaruzzaman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The XRD patterns of MCM-41 and Al-MCM-41 showed a decrease in intensity with a high amount of Fe added. In our previous work, the catalytic performances of bimetallic Pt-Fe catalysts with 5 wt.% Fe supported on RH-MCM-41 and Al-RH-MCM-41 were compared, and Pt-Fe/RH-MCM-41 gave a higher conversion [16]. Although it was expected that supports with higher acidity would be more active, the addition of Al resulted in a significant decrease in the surface area of MCM-41, which could explain the poorer performance.…”
Section: Introductionmentioning
confidence: 99%
“…After calcination to eliminate the organics, metallic impurities such as oxides of alkali metals are removed by leaching with NaOH solution at temperatures between 100 and 200 o C for 1 h. Direct recovery of silica by precipitation from the basic solution is achieved by addition of drops of sulfuric acid to the hot basic solution, followed by thermal treatment at 110 o C [34]. Several products of commercial interest such as silicon carbide (SiC) used as semiconductors, pozzolan in cement manufacturing, and recently, sodium silicate in the preparation of silica-based mesoporous materials have been reported [35][36][37][38][39][40][41][42]. [42] demonstrated that RHA silica generated from biomass power plant can be used as silica framework for synthesis of MCM-41-type material with crystallinity characteristics and porosity similar to those synthesized from commercial silica.…”
Section: Utilization Of Silica Framework From Biomass Residuesmentioning
confidence: 99%